How Flexible are the Prokaryote Consortia in the Extreme Habitat of the Copahue Geothermal System? - Zurakoski, Natasha (2013)
Microbial consortia taken from an extreme environment were grown at different temperatures and enrichment media. The consortia response to environmental changes was evaluated in order to investigate their metabolic flexibility. The molecular technique, DGGE (denaturing gel gradient electrophoresis) was carried out to evaluate the biodiversity. The results show that each consortium was able to grow according to the available resources, demonstrating their flexibility. A selective development was detected when growing conditions were similar to those found in the natural environment even though some species were able to grown even in conditions far away from those present in the sampling sites.